Youth retail tobacco access in Canada: Regional variation, perceptions, and predictors from YSS 2010/2011. (December 2015) - Minaker, Leia M.; Soni, Shilpa; Nguyen, Nghia; Manske, Steve
Abstract: Purpose: Retail tobacco access is an important determinant of youth smoking prevalence. This study examines perceptions of ease in obtaining cigarettes and how prevalence of self-reported retail tobacco access among youth smokers varies by province in Canada. Additionally, relevant retail experiences, such as being asked for identification by a store clerk, are described. Methods: Data from grades 9–12 students who participated in the 2010/2011 Youth Smoking Survey, a nationally generalizable sample of Canadian students (n = 31396) were used to examine retail tobacco access and related experiences. Logistic regression models were used to examine differences in retail tobacco access and retail tobacco experiences by sociodemographic and regional characteristics. Results: 79% of students who never smoked thought it would be easy to get cigarettes. About one-quarter of smokers reported usually buying cigarettes from stores, and the percent of student smokers usually buying cigarettes in stores ranged from 16% in British Columbia to 36% in Quebec. Compared to grade 9 students, grade 12 students had higher odds of report being asked for identification (OR = 6.3, 95% CI 1.9–21.5). Conclusions: Retail tobacco access appears to be a significant source of cigarette access among Canadian youth. Retail tobacco access varies significantly by province, which suggests provincial policies should be strengthened. Highlights: A quarter of Canadian grades 9-12 smokers usually buy cigarettes at a store Provincial youth retail tobacco access ranges from 16% in BC to 26% in QC 80% of never smokers thought it would be easy to get cigarettes to smoke